(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: Survey on the rate of knowledge, attitude, and practice of antibiotic use among caregivers of children with congenital heart disease in Pediatric Cardiac Surgical ICU. Subjects and research methods: A descriptive cross-sectional study was carried out involving direct interviews with 76 caregivers of children undergoing treatment in the Pediatric Cardiac Surgery ICU. The study was conducted from August 2025 to October 2025. Results: The proportion of caregivers demonstrating adequate knowledge about antibiotic use was 37,3%. Besides, 92,5% exhibited appropriate attitudes, and 80,5% reported proper practices concerning antibiotic administration. Conclusion: The findings indicate a high prevalence of appropriate attitudes and practices regarding antibiotic use among caregivers of children with CHD; however, the level of knowledge remains suboptimal. Targeted educational programs are critically needed to enhance caregivers’ pharmacological knowledge of appropriate antibiotic use.